Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2147/cia.s104783
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with postoperative complications and 1-year mortality after surgery for colorectal cancer in octogenarians and nonagenarians

Abstract: PurposeTo identify the factors affecting 30-day postoperative complications and 1-year mortality after surgery for colorectal cancer in octogenarians and nonagenarians.MethodsBetween 2005 and 2014, a total of 204 consecutive patients aged ≥80 years who underwent major colorectal surgery were included.ResultsOne hundred patients were male (49%) and 52 patients had American Society of Anesthesiologists (ASA) score ≥3 (25%). Combined surgery was performed in 32 patients (16%). Postoperative complications within 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 40 publications
8
37
1
Order By: Relevance
“…We did not include age as a risk factor because all patients were between 20 and 75 years old. The studies of Kim and Kim and Ragg et al, respectively, showed that age greater than 90 years old and age greater than 75 years old to be one risk factor for overall postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include age as a risk factor because all patients were between 20 and 75 years old. The studies of Kim and Kim and Ragg et al, respectively, showed that age greater than 90 years old and age greater than 75 years old to be one risk factor for overall postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two studies with 30-day mortality as an outcome, scoring ASA >2 was the only predictor that was significantly associated with increased 30-day mortality [22,26].…”
Section: Asamentioning
confidence: 90%
“…Compared to open surgery, laparoscopic surgery was well tolerated and found to be significantly protective, with patients half as likely to develop Clavien-Dindo II complications (OR: 0.49) [22]. Tan et al [20] showed similar results (OR: 0.625).…”
Section: Type Of Surgerymentioning
confidence: 96%
See 2 more Smart Citations